Nazariyat Ibnu Bajah ‘an al-Nafs - Rif’at Husnul Ma’afi; Faiq Nebukadnezar (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
The soul is one of the central issues focused on by prominent Muslim philosophers due to its crucial role in constructing thoughts, acts, and human behaviour. One of these eminent philosopher was Abu Bakr Muhammad bin Yahya bin Bajah or who is more commonly known as Ibnu Bajah. Although he discussed the soul at great length, he did not explicitly define what it is, such as what other philosophers had tried to do. However, Ibnu Bajah expressed what is known about the soul by the improvements of al-Jism al-‘Ali (the Automatic Body), which has 4 kinds of strengths: to consume, to sense, to move, and to talk. Man with these in one word herit strengths are able to direct his body to grow and live in order to fulfill his physical needs, and at the same time pursue and attain information, knowledge, and understanding. It is important to acknowledge that the human mind reaches its perfection with the aid of rational knowledge. The rational knowledge enables them to understand the matter essentially, and when man may attain ultimate happiness. Therefore human perfection is the combination and interrelation between the active mind and rational view working together. This correlation will be attained gradually, with knowledge representing rational objects from material objects, then transcending it to relate with the active mind. Human knowledge then begins from the sense of representation of the object physically, abstracting its representation by the power of imagination, interpreting the meaning in the mind from the senses. Thus if will deliver humans to the right knowledge of himself and the active mind.